2020
DOI: 10.1002/ange.202006890
|View full text |Cite
|
Sign up to set email alerts
|

Light‐Induced Self‐Escape of Spherical Nucleic Acid from Endo/Lysosome for Efficient Non‐Cationic Gene Delivery

Abstract: Developing non-cationic gene carriers and achieving efficient endo/lysosome escape of functional nucleic acids in cytosol are two major challenges faced by the field of gene delivery. Herein, we demonstrate the concept of self-escape spherical nucleic acid (SNA) to achieve light controlled noncationic gene delivery with sufficient endo/lysosome escape capacity. In this system, Bcl-2 antisense oligonucleotides (OSAs) were conjugated onto the surface of aggregationinduced emission (AIE) photosensitizer (PS) nano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Nowadays, various AIEgens-based nanoscale fluorescent probes, namely AIE nanodots, have been widely developed as the novel IGDD system due to their high sensitivity and spatio-temporal resolution [ 378 , 379 ]. As for the TOs delivery, AIE nanodots can either be fabricated by incorporating AIE dyes to the preformed nanoparticles or through self-assembling AIE-moiety-containing amphiphilic conjugates [ [380] , [381] , [382] , [383] ].…”
Section: Nanoparticles-based Delivery Of Tosmentioning
confidence: 99%
See 1 more Smart Citation
“…Nowadays, various AIEgens-based nanoscale fluorescent probes, namely AIE nanodots, have been widely developed as the novel IGDD system due to their high sensitivity and spatio-temporal resolution [ 378 , 379 ]. As for the TOs delivery, AIE nanodots can either be fabricated by incorporating AIE dyes to the preformed nanoparticles or through self-assembling AIE-moiety-containing amphiphilic conjugates [ [380] , [381] , [382] , [383] ].…”
Section: Nanoparticles-based Delivery Of Tosmentioning
confidence: 99%
“…While upon visible-light irradiation, TPECM produced ROS, leading to the disruption of the endo/lysosomal membranes and cleavage of the polymer which thus caused the DNA release for transcription. In a recent study, the same group reported another type of AIE-nanodots which also demonstrated a ROS-responsive endo/lysosomal escape properties [ 382 ]. Different with previous study, here they covalently immobilized the anti-apoptotic Bcl-2 antisense oligonucleotides (OSA) to the AIE nanodots via the Click reaction.…”
Section: Nanoparticles-based Delivery Of Tosmentioning
confidence: 99%
“…Spherical nucleic acids (SNAs) are densely packed linear nucleic acids in three-dimensional, spherical geometry and were first established by Mirkin et al in 1996. , After that, they were widely used in biomedical research and clinical settings, such as biosensing, gene regulation, immunotherapy, , and vaccines . The structure of SNAs typically contains two components: a nanoparticle core and an oligonucleotide shell.…”
Section: Introductionmentioning
confidence: 99%
“…Herein, we design the hierarchical self‐assembly of tetraphenylethylene (TPE)‐featured MOCs into fluorescent SNPs (FSNPs) for delivering protein into neural cells, which is a hard‐to‐transfect cell line using conventional strategy. In addition, TPE is known for its unique aggregation‐induced emission (AIE) characteristics, it shows significantly enhanced fluorescence emission in the aggregation state or in coordinated supramolecular cages than that in a solution [22–26] . We therefore hypothesized that the unique fluorescence of TPE‐featured SNPs may allow the trafficking of intracellular protein delivery using fluorescent microscopy imaging.…”
Section: Introductionmentioning
confidence: 99%